Tranformasi Pemanfaatan Lahan di Kalimantan: Studi Perubahan di Kalimantan Tahun 1800-2012 - Muhamad Arief Rafsanjani (Wacana: Jurnal Ilmu Sosial dan Ilmu Politik Interdisiplin, 2021)
Kalimantan has undergone significant land changes in the last two decades. Change has a historical process that has led to wider land intensification. This history is full of economic improvement matters, so that the land transformation that occurred in Kalimantan cannot be separated from the presence of the market. Starting from the colonial phase through rubber crops, logging for the use of the logging industry to the oil palm plantation industry